Jurisprudence worship in Islamic education for the primary stage (analytical study) (Journal of the College of Basic Education, 2025)
Jurisprudence is an important part of Islamic education. It connects man with his God, contributes to the building of his faith and moral personality, promotes spiritual and social values and, since the primary stage is the cornerstone of the building of the child's personality and directs him towards a proper understanding of worship; That was why the doctrine had to be studied in the subject of Islamic education for the elementary stage. and indicate the topics of worship and how it is raised and how it affects, and its relevance to the pupils' stage And this study dealt with the concept of doctrine and the purpose of teaching it, The purpose of this study is to familiarize itself with jurisprudence and to explore its topics and provisions; Methods and methods used when they are introduced, using that analytical approach, This study contained an introduction and two-pronged researchers. In the conclusion, the most important conclusions and recommendations were mentioned, including that religious worship was the words and deeds of Muslims. and that Islamic education materials came in such a way as to make students more loving and accepting of those worships, It is limited to its basic concepts, focusing on streamlining and clarifying them and indicating their relevance and provisions, so that they can exercise them consciously and consciously.